2021
DOI: 10.1111/ppc.12984
|View full text |Cite
|
Sign up to set email alerts
|

A study on the adaptation of the HIV/AIDS‐related Stigma Scale into Turkish

Abstract: Purpose This study aims to test the validity and reliability of the Turkish version of the HIV/AIDS‐related Stigma Scale. Design and Methods The study has a methodological design. The sample included a total of 428 participants. of the participants, 198 were HIV/AIDS patients, 230 were HIV‐negative individuals. The data were analyzed using the Exploratory and Confirmatory Factor Analysis. Findings The Turkish version of the HIV/AIDS‐related Stigma Scale was found to be valid and reliable for the Turkish societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The CFA results for the two-factor model indicated the model was a good fit: SRMR=0.038<0.05, RMSEA=0.12<1.0, GFI=0.912>0.800, NFI=0.883>0.800, TLI=0.845>0.800, CFI=0.888>0.850. 42–44 Furthermore, although there is a positive correlation between these two dimensions, they represent distinct facets of stigma and may be considered independent. This finding provides further evidence for the necessity of analyzing these two dimensions separately ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CFA results for the two-factor model indicated the model was a good fit: SRMR=0.038<0.05, RMSEA=0.12<1.0, GFI=0.912>0.800, NFI=0.883>0.800, TLI=0.845>0.800, CFI=0.888>0.850. 42–44 Furthermore, although there is a positive correlation between these two dimensions, they represent distinct facets of stigma and may be considered independent. This finding provides further evidence for the necessity of analyzing these two dimensions separately ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40][41] The critical values for acceptable model fit used in the present study were SRMR<0.08, RMSEA≤1.0, GFI≥0.80, NFI≥0.80, TLI≥0.80, CFI≥0.85. [42][43][44] Composite Reliability (CR), Average Variance Extracted (AVE) and Heterotrait-Monotrait ratio (HTMT) values of scale were calculated to test convergent and divergent validity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding model fit, the values are considered as follows; χ ²/df <3 perfect fit, RMSEA 0.08 and below good fit, CFI 0.90 and above good fit, NFI and CFI 0.95 and above perfect fit, IFI 0.90 and above good fit, GFI 0.90 and above good fit (Bahar and Cal, 2022). Coelho et al (2021) reported the following fit indices for the original scale: GFI = 0.96, CFI = 0.98 and RMSEA = 0.08.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring the effectiveness of HIV stigma-reducing interventions using validated measures can support local programmes advocating for additional resources and enable the identification and sharing of best practice. The HIV Stigma Scale is a reliable and validated measure of HIV-related stigma [ 57 ], which could be adapted for use in CEE in the same way that it has been in Turkey [ 58 , 59 ], Ukraine [ 29 ], and Japan [ 60 ]. An adapted HIV Stigma Scale to monitor stigma related to pre-exposure prophylaxis use has also been developed [ 61 ].…”
Section: Discussionmentioning
confidence: 99%